2020
DOI: 10.4103/jpbs.jpbs_188_20
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a pharmacist-led warfarin educational video in a Saudi setting

Abstract: A BSTRACT Context: Internationally, various warfarin education strategies have been described in the medical literature and delivered by a variety of health-care providers. However, none of these were tested in a Saudi setting. Aim: The aim of this study was to assess the impact of pharmacist interventions via an educational video on improving patient knowledge of and satisfaction with warfarin therapy and the international normalized ratio (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Shilbayeh concluded that a pharmacist-led audio-visual intervention via an educational video and a brochure effectively improved patients’ knowledge retention and satisfaction with warfarin therapy benefits [ 17 ]. However, these reported data show a trend different from our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Shilbayeh concluded that a pharmacist-led audio-visual intervention via an educational video and a brochure effectively improved patients’ knowledge retention and satisfaction with warfarin therapy benefits [ 17 ]. However, these reported data show a trend different from our findings.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1432 studies were found, but only studies that evaluated the impact of ambulatory care clinical pharmacists on patients' outcomes were included (Table 2). 11‐22 …”
Section: Methodsmentioning
confidence: 99%
“…Currently, in KSA, several well‐established ambulatory care pharmacy clinics specialize in medication therapy management (MTM), anticoagulation, and diabetes, all of which have been proven to enhance clinical patient outcomes and patient satisfaction 11‐22 . A review of these clinics is presented in (Table 2).…”
Section: Methodsmentioning
confidence: 99%